(untitled) (World Science, 2020)
Aim. To improve the results of surgical treatment of umbilical hernias nanomodified polypropylene mesh. Materials and methods. The analysis of laparoscopic operacione treatment of 126 patients with HAL with DRA of has been performed. Depending on the type of mesh used during surgical treatment, patients were divided into 2 groups. Results and discussion. Statistically significant results were obtained in patients of Group I compared to Group II. Conclusions. Laparoscopic operacione treatment of HAL with DRA using nanomodified polypropylene mesh antiseptic the use of the classical polypropylene mesh, namely, reducing the freguency postoperative wound complications.